Sams teach yourself Microsoft Visual C♯ 2005 in 24 hours : complete starter kit - Foxall, James D. (Sams teach yourself in 24 hours series., 2006)
Looking to break into C# programming? Sams Teach Yourself Visual C# 2005 in 24 Hours, Complete Starter Kit is a valuable resource. You will start by learning the basics of the Visual C# environment and begin to build working programs very quickly. As the programs become more complex, you will discover more of the advanced features of the C# programming language and the Visual C# tool. Set with the practical goal of providing you with a solid foundation from which to grow and develop your C# programming skills, this book is perfect for use in a professional setting or for use with personal projects. The accompanying CD includes Visual C# 2005 Express Edition, a streamlined, easy-to-use development tool that makes Windows programming with C# fun. Jump in with both feet with the help of Sams Teach Yourself Visual C# 2005 in 24 Hours, Complete Starter Kit.